2011
DOI: 10.1007/8904_2011_96
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Like Therapy with Tetrahydrobiopterin in Clinical Trials for Phenylketonuria: Is Genotype a Predictor of Response?

Abstract: Prospectively enrolled phenylketonuria patients (n ¼ 485) participated in an international Phase II clinical trial to identify the prevalence of a therapeutic response to daily doses of sapropterin dihydrochloride (sapropterin, KUVAN ® ). Responsive patients were then enrolled in two subsequent Phase III clinical trials to examine safety, ability to reduce blood Phenylalanine levels, dosage (5-20 mg/kg/day) and response, and bioavailability of sapropterin. We combined phenotypic findings in the Phase II and II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
(76 reference statements)
1
15
1
Order By: Relevance
“…A negative inter-allelic complementation could have a role, preventing better response [51]. In addition, IVS8 − 7 mutation was shown not to be BH 4 responsive in a functionally hemizygous patient, which is in accordance with a single previous report [48]. The BH 4 responsiveness in splice-site mutations could be explained by the existence of residual normal splicing and/or transcripts with a residual enzyme function in those cases [52].…”
Section: Bh 4 -Responsivenesssupporting
confidence: 77%
See 1 more Smart Citation
“…A negative inter-allelic complementation could have a role, preventing better response [51]. In addition, IVS8 − 7 mutation was shown not to be BH 4 responsive in a functionally hemizygous patient, which is in accordance with a single previous report [48]. The BH 4 responsiveness in splice-site mutations could be explained by the existence of residual normal splicing and/or transcripts with a residual enzyme function in those cases [52].…”
Section: Bh 4 -Responsivenesssupporting
confidence: 77%
“…Their effect depended on the other mutations in the genotype as reported previously [12,27,35,36,38,39,44]. The p.L48S mutation showed a response and slow-response in combination with IVS4 − 5 C>G mutation; unlike in previous reports no response was observed in combination with p.S349P which is a null mutation [48,49]. The p.R158Q mutation was responsive in all four cases with p.E390G, but as previously suggested not in functionally hemizygous patients (combination with p.R408W or possibly with p.R157S) [12,38,39]; furthermore, a slow-response was observed in combination with IVS10 − 3 C>T. The p.R261Q mutation is one of the very few responsive mutations located in the cofactor binding domain [35]; however, the response was observed only in the combination with p.E390G, but not in a combination with a null mutations (EX5del955 and p.R408W), which confirmed most previous reports [36,38].…”
Section: Bh 4 -Responsivenesscontrasting
confidence: 37%
“…The outcome of the BH 4 test was correlated with the single allele variation or with the genotype [Dobrowolski et al., ; Karacic et al., ; Quirk et al., ; Sarkissian et al., ; Zurflüh et al., ] and for a number genotypes this was found to be a useful complementary tool to BH 4 challenge (Table ). Dobrowolski et al.…”
Section: Phenotype–genotype Correlation and Bh4 Responsiveness Predicmentioning
confidence: 99%
“…Sarkissian et al. () reported p.V388M as an unresponsive mutation, whereas in the BIOPKU database, of the 14 homozygous patients for the p.V388M mutation tested for BH 4 responsiveness, eight (57.14%) were responsive and two (14.29%) were slow responders. Zurfluh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sarkissian et al. () analyzed the genotypes of patients that participated in the clinical trials of sapropterin, a synthetic pharmacological form of BH 4 (6 R ‐L‐ erythro ‐5,6,7,8 tetrahydrobiopterin dihydrochloride). There are some inconsistencies between these authors’ findings and those reported at the BIOPKU database and by Zurfluh et al.…”
Section: Discussionmentioning
confidence: 99%